P.080 Cognitive Profile, Disease Characteristics, and Neuroimaging Findings in Susac Syndrome: A Case Series of Seven Participants from British Columbia. (November 2021) - Chivukula, P; Chan, J; Johnson, P; Bower, G; Li, D; Lee, J; Vavasour, I; Traboulsee, A; Laule, C; Kolind, S; Woolfenden, A; Carruthers, R
Abstract : Background: Susac Syndrome (SuS) is a rare autoimmune disorder of the cerebral, retinal, and inner ear microvasculature. One of the cardinal manifestations of central nervous system (CNS) involvement is encephalopathy, however the cognitive profile in SuS is poorly characterized in the literature. Methods: In this cross-sectional case series of seven participants diagnosed with Susac Syndrome in remission in British Columbia, we use a battery of neuropsychological testing, subjective disease scores, and objective markers of disease severity to characterize the affected cognitive domains and determine if any disease characteristics predict neuropsychological performance. We also compare this battery of tests to neuroimaging markers to determine if correlation exists between radiographic markers of CNS disease and clinical evaluation of disease severity. Results: There were a variety of cognitive deficits, with memory and language dysfunction being the most common. Despite the variability, performance on some neuropsychological tests (MoCA) correlated to markers of functional disability (EDSS). Additionally, MoCA and EDSS scores correlated with neuroimaging findings of both corpus callosum and white matter changes. Finally, psychiatric scores correlated with participant reported scores of disease severity. Conclusions: There is a relationship between cognitive deficits, subjective and objective disease disability, and neuroimaging findings in Susac Syndrome.